THE EFFECT OF QUALITY SERVICE AND EMOTIONAL PROXIMITY ON CUSTOMER LOYALTY AND SATISFACTION AS AN INTERVENING VARIABLE AT PT PNM CIREBON BRANCH - Roshadianto, Toto Ryan; Wahyuni, Dr. Sri (jfpublisher, 2023)
Banks are one of the financial institutions engaged in services that can provide the 'excellent service' to compete with increasing competition. Therefore, to maintain and increase its customers, banks need to maintain a positive image within the community. Maintaining this image can be achieved through product quality, quality service, and security order. This research aims to determine the effect of quality service and emotional proximity on customer loyalty and customer satisfaction as an intervening variable at PT PNM Cirebon Branch. This research used descriptive quantitative approach with Structural Equation Modeling (SEM) using AMOS 26 program. Sobel test was conducted to determine the effect of mediation or intervening. The unit of analysis used is all customers of PT PNM Cirebon Branch who have topped up at least twice. The sample consisted of 150 respondents who filled out the questionnaire online. This research is expected to prove that quality service and emotional proximity have a positive and significant effect on customer satisfaction and loyalty.